Management Issues Regarding Caligidosis Treatment on Salmon Farms in Chile Affected by Infection Salmon Anaemia Virus (Isav), Piscirickettsia Salmonis and Neoparamoeba Perurans - Cortez-San Martin, M; Robles-Planells, C (Elsevier Ltd, 2016)
Chile is one of the world s most prolific producers of farmed salmon, but has suffered great economic losses due to fish diseases. In this study, the interactions of treatments for the caligidosis agent Caligus rogercresseyi and major diseases in salmon aquaculture caused by Piscirickettsia salmonis, Infectious Salmon Anaemia Virus and Neoparamoeba perurans were determined. This information is essential to develop an integrated management strategy in Chile. Immunosuppression due to fish stress, increased by frequent chemical baths to treat C. rogercresseyi, was considered to be the main source of chronic caligidosis and high prevalence of other diseases. P. salmonis and pathogenic ISAV were detected using PCR analysis at all farms sampled, but N. perurans at one farm in April only. In 2011, individuals of Oncorhynchus mykiss with gill pathology not caused by N. perurans and receiving chemical baths at Farm 1 were affected by 100% prevalence of sea lice. Similar prevalence was observed on Salmo salar at Farm 2, which did not receive bath treatments. Both farms were under similar oceanographic influence. A prevalence of 80% of a pathogenic strain of ISAV, but without clinical symptoms, was detected at Farm 2, combined with low sea lice presence and almost complete absence of ovigerous females (OF) even though no treatment had been applied. S. salar sampled at Farm 3 in 2013 were also chronically infested with sea lice despite routine chemical treatment baths. P. salmonis was correlated with the increase in OF and chalimii. It was concluded that chemical baths to treat sea lice triggered fish mortality concomitantly with AGD due to prior gill damage. Fish stress conditions elicited by fish-gill disease, fish maturation and P. salmonis were related to an increase of ovigerous sea lice females. The decrease in recurrent and routine chemical baths allowed a reduction of sea lice reproduction and, most likely, of ISAV outbreaks. © 2016 Elsevier Ltd.
Keywords: Caligus rogercresseyi; ISAV; Piscirickettsiosis; AGD; Co-infections; Lice bath-treatments; Integrated management